Keefektifan Teknik Modeling Berbasis Sinema Edukasi untuk Meningkatkan Efikasi Diri Akademik Siswa SMP - Ragil, Endang; Ariyanto, Restu Dwi; Ratnawati, Vivi; Ningsih, Risaniatin; Valdino, Dias Rendy (Universitas Nusantara PGRI Kediri, 2019)
Phenomenon Students with low academic self-efficacy tend to avoid difficult tasks, because the task is considered a threat to him. Students have low aspirations and commitment in achieving the learning goals they set. When faced with difficult tasks, student is busy thinking about the deficiencies that exist in him, the disturbances he faces, and all the results that can be detrimental. When faced with difficult tasks, students with low self-efficacy will reduce their efforts and tend to give up quickly and slow to fix or regain their self-efficacy when experiencing failure. So we need a technique to reduce these rights, one of which is the application of modeling techniques based on cinema of educational. This study aims to determine the effectiveness modeling techniques based on cinema of educational to improve students' academic self-efficacy. This research method uses an experimental research approach with the type of one group pretest-posttest design. The conclusion of the study showed that the Paired Samples Test score was 0.026 <0.05. These results can be concluded that modeling techniques based on cinema of educational are effective for increasing the academic self-efficacy of junior high school students.